MICRO TEACHING SKILLS AND TEACHING READINESS OF ENGLISH STUDY PROGRAM STUDENTS : A CORRELATION STUDY - Salwiyatul Jannah; Afrianto Daud; Novitri Novitri (Tell-us Journal)
This study was conducted to determine the correlation between micro teaching skills and teaching readiness of English Study Program students of Riau University batch 2019. The research design was a descriptive correlation that focused on the quantitative approach. A total of 54 students were selected using proportional random sampling technique as the sample of this study. The researcher used two research instruments to collect data; questionnaire and documentation. The validity and reliability of the questionnaire data for teaching readiness have been tested. Statistical analysis applied the Pearson product-moment formula using IBM SPSS Statistics to analyze the correlation between micro teaching skills and teaching readiness of English Study Program students of Riau University batch 2019.  The results showed that the Pearson rcount correlation value of 0.879 was higher than the rtable of 0.268 at the 0.05 confidence level, indicating that the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected. The research findings show that there is a positive and significant correlation between micro teaching skills and teaching readiness of English Study Program students of Riau University batch 2019. This shows that the higher the micro teaching skills obtained, the higher their teaching readiness of students will increase.